A Switching Performance Index-Driven Escaping-Chasing Control of Networked Control Systems Under Triggered DoS Attacks - Xing, Ning; Zhang, Hai-Tao (IEEE transactions on control of network systems, 2025)
In this article, an escaping-chasing control problem under triggered denial-of-service (DoS) attacks is addressed. A switching performance index-driven escaping-chasing path planning method is designed, and the tracking error systems are accordingly established. The analytical challenge lies in the tricky coupling between the performance index-driven and the DoS attack-driven switches. To this end, with the assistance of the average dwell time analytical method, the restrictions on both the DoS attack intensity and the switching frequency between "chasing unawareness" and "chasing awareness" are given to guarantee finite-time capturing of the chaser. Finally, simulations are conducted to verify the effectiveness of the proposed escaping-chasing control method.